Determination of Prospective Science Teachers' Level of Knowledge about Thermodynamics and Their Reasoning with Daily Life Examples - Eser Ültay; Ümmü Gülsüm Durukan; Neslihan Ültay (Universitas Pendidikan Indonesia, 2021)
The aim of this study was to determine the relationship between environmental problems and thermodynamics of prospective science teachers. The study was conducted with the case study method. The sample consists of 74 senior prospective science teachers studying in Science Teaching Department in the faculty of education of a state university in Turkey in spring semester of 2018-2019 academic year. The first part of the data collection tool consisted of four open-ended questions and it was the form in which the prospective science teachers were asked to explain the laws of thermodynamics. In the second part of the data collection tool, there were eleven open-ended questions which were expected to be explained by the laws of thermodynamics of the given environmental problems. As a result of the study, prospective science teachers were found to have difficulty applying any laws of thermodynamics to a daily event or environmental problem.